A Comprehensive Review of Color Image Encryption Technology - Dawood, Alyaa I.; Thabit, Qabeela Q.; Fahad, Taqwa O. (Basrah Journal for Engineering Sciences, 2023)
Today, with the continuous increase in the use of computer networks and the rapid evolution of information technologies. The secure transmission of data over the Internet has become an urgent necessity to preserve the privacy of users and protect sensitive information from theft and distortion. images are most of this transferred data, so it was necessary to protect it by encrypting them using algorithms that ensure the protection of information access to the receiver. Color images contain sensitive information and details that must be secured and protected. This paper produces a comprehensive review of image encryption methods and classifies them based on various concepts such as chaotic maps, DNA, etc. with comparisons between existing approaches to accessing different security parameters. Additionally, the types of encryption keys were reviewed along with some common types of attacks and the most important methods for measuring encryption efficiency.